RESEARCH ON SOCIAL-PSYCHOLOGICAL FEATURES OF SERVICEMEN’S ADAPTATION TO MILITARY SERVICE - Karyna Andriivna Yarmuratii (Insight: the psychological dimensions of society, 2019)
Purpose. To determine the nature of impact of personal features on social-psychological adaptation of servicemen called to military service.Methods. The research uses the following diagnostic methods: the questionnaire by “A personal scale of anxiety symptoms”; Rosenzweig’s picture test; the methods for diagnosing value orientations (М. Rokeach); J. Moreno’s sociometric test (A. A. Rean); the methods for determining adequacy of realizing one’s status in a group’s status hierarchy (a modified variant of A. S. Sylakov’s methods).Results. The study determines the factors, contributing to the formation of soldiers’ subjectivity under variative service conditions and under conditions which support this process for servicemen practically: the formation of an “attractive” image of a subunit, membership of a platoon, a company, raising personal authority in a military staff, ideally – the creation of a military socio-cultural space with optimal combination of mental and social aspects, the availability of a wide range of activities, the involvement of soldiers in a wide scope of activities, which go beyond the limits of a subunit.Conclusions. The paper presents the research on social-psychological features of servicemen’s adaptation to military service. It offers a number of practical recommendations for educational structures of the Armed forces about the development of pedagogical technologies, aimed at personal adaptation of servicemen called to military service to different qualitatively new activities for them. It stresses that adaptation to military service should be changed from the level of a spontaneous and chaotic approach to education to the level of professional pedagogy, to the level of psychological-pedagogical technologies. The study substantiates that the development of psychological-pedagogical technologies considering the adaptation features of servicemen called to military service causes a purposeful changes in the characteristics of personality, in particular, it allows reducing the level of anxiety, changing the mechanism of interaction with a frustrator. It establishes that when developing the procedures associated with servicemen’s adaptation, it is necessary to take into consideration, that commanders’ psychological-pedagogical impact should be developed according to the changes of servicemen’s personal features.